Spin Noise Detection of Nuclear Hyperpolarization at 1.2 K. Issue 18 (13th November 2015) - Pöschko, Maria Theresia; Vuichoud, Basile; Milani, Jonas; Bornet, Aurélien; Bechmann, Matthias; Bodenhausen, Geoffrey; Jannin, Sami; Müller, Norbert
Abstract: We report proton spin noise spectra of a hyperpolarized solid sample of commonly used "DNP (dynamic nuclear polarization) juice" containing TEMPOL (4‐hydroxy‐2, 2, 6, 6‐tetramethylpiperidine N ‐oxide) and irradiated by a microwave field at a temperature of 1.2 K in a magnetic field of 6.7 T. The line shapes of the spin noise power spectra are sensitive to the variation of the microwave irradiation frequency and change from dip to bump, when the electron Larmor frequency is crossed, which is shown to be in good accordance with theory by simulations. Small but significant deviations from these predictions are observed, which can be related to spin noise and radiation damping phenomena that have been reported in thermally polarized systems. The non‐linear dependence of the spin noise integral on nuclear polarization provides a means to monitor hyperpolarization semi‐quantitatively without any perturbation of the spin system by radio frequency irradiation. Abstract : Dynamic nuclear polarization : It is demonstrated that during microwave irradiation of "DNP juice" at 1.2 K the proton spin noise power depends on the hyperpolarization achieved. Positive and negative polarization levels obtained by microwave irradiation at different frequency offsets from the electron Larmor frequency give rise to dip‐ and bump‐shaped noise peaks, respectively.